Paecilomyces clematidis (Eurotiales, Thermoascaceae): a new species from Clematis root - Spetik, Milan; Berraf-Tebbal, Akila; Gramaje, David; Eddine Mahamedi, Alla; Stusková, Katerina; Burgova, Jana; Eichmeier, Ales (Phytotaxa, 2022)
During a survey of endophytic fungi associated with ornamental plants in the Czech Republic, Paecilomyces-like strains were isolated from the root of Clematis. Analyses based on a combined internal transcribed spacer region (ITS), beta-tubulin (tub2) and calmodulin (CaM) sequence data matrix were applied to infer the phylogenetic position of these isolates. The novel species is characterized by phialides with a cylindrical basal portion tapering to a thin long neck producing pyriform conidia in chains. The new species is introduced with comprehensive descriptions, illustrations and a phylogenetic tree herein. Two primer pairs targeting the partial CaM gene, cm1F/cm1R and cm2F/cm2R, were designed in this study.